Bayesian analysis made simple an Excel GUI for WinBUGS - Woodward, Phillip (Boca Raton, FL CRC Press, 2012)
"Although the popularity of the Bayesian approach to statistics has been growing for years, many still think of it as somewhat esoteric, not focused on practical issues, or generally too difficult to understand.Bayesian Analysis Made Simple is aimed at those who wish to apply Bayesian methods but either are not experts or do not have the time to create WinBUGS code and ancillary files for every analysis they undertake. Accessible to even those who would not routinely use Excel, this book provides a custom-made Excel GUI, immediately useful to those users who want to be able to quickly apply Bayesian methods without being distracted by computing or mathematical issues.From simple NLMs to complex GLMMs and beyond, Bayesian Analysis Made Simple describes how to use Excel for a vast range of Bayesian models in an intuitive manner accessible to the statistically savvy user. Packed with relevant case studies, this book is for any data analyst wishing to apply Bayesian methods to analyze their data, from professional statisticians to statistically aware scientists"--Provided by publisher.
"Preface Although the popularity of the Bayesian approach to statistics has been growing rapidly for many years, among those working in business and industry there are still many who think of it as somewhat esoteric, not focused on practical issues, or generally quite difficult to understand. This view may be partly due to the relatively few books that focus primarily on how to apply Bayesian methods to a wide range of common problems. I believe that the essence of the approach is not only much more relevant to the scientific problems that require statistical thinking and methods, but also much easier to understand and explain to the wider scientific community. But being convinced of the benefits of the Bayesian approach is not enough if the person charged with analyzing the data does not have the computing software tools to implement these methods. Although WinBUGS (Lunn et al. 2000) provides sufficient functionality for the vast majority of data analyses that are undertaken, there is still a steep learning curve associated with the programming language that many will not have the time or motivation to overcome. This book describes a graphical user interface (GUI) for WinBUGS, BugsXLA, the purpose of which is to make Bayesian analysis relatively simple. Since I have always been an advocate of Excel as a tool for exploratory graphical analysis of data (somewhat against the anti-Excel feelings in the statistical community generally), I created BugsXLA as an Excel add-in. Other than to calculate some simple summary statistics from the data, Excel is only used as a convenient vehicle to store the data, plus some meta-data used by BugsXLA, as well as a home for the Visual Basic program itself"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Microsoft Excel (Computer file).; WinBUGS; Bayesian statistical decision theory